Faktor-Faktor yang Mempengaruhi Kewajiban Pengungkapan dalam Laporan Keuangan: Studi Empiris pada Perusahaan Pulp dan Kertas yang Terdaftar di BEI - Fidiatur Fitrifiani; Ridwan (Jurnal Buana Akuntansi, 2020)
This study objectives to determine the factors that affect mandatory disclosure in the financial statements consisting of leverage, liquidity, profitability, public share ownership, and company status. The data used in this study are secondary in the form of financial reports and annual reports. The number of companies studied was eight companies in 2013-2017 and the number of samples is counted to 40 observations. The sampling method used in this study was purposive sampling using certain criteria. The analysis technique used is panel data regression analysis, estimation test for model selection, classic assumption test with a hypothesis test. The results of the research analysis showed that partial leverage, liquidity, profitability, and public share ownership had no significant and negative effect on mandatory disclosure in the financial statements while company status did not have a significant effect but had a positive direction mandatory disclosure in the financial statement.